POLA KOMUNIKASI PELATIH DAN ATLET DALAM MENCAPAI PRESTASI (STUDI PADA KLUB BULUTANGKIS PB. PORWAJA) - Puspitayanti, Putu Desthin; Purnawan, Ni Luh Ramaswati; Gelgel, Ni Made Ras Amanda (E-Jurnal Medium, 2025)
PB Porwaja is the oldest badminton club in the capital of Bali province, with great potential for regenerating and defending badminton sports to always be the most demanding and to build the soul of a hardy and competitive local, national and international competition. It is a descriptive qualitative study. Moloeng (2002 :11) says that decompression research on data patterns of words and pictures instead of Numbers caused by the application of qualitative methods.   Furthermore, all collected up is likely to be the key to what has been studied. The removal of samples or data sources on this study is strictly sampling, one of the stau sampling techniques where researchers determine the taking of samples by establishing specific properties consistent with the purpose of the study and are expected to provide answers to the research. Interpersonal communication patterns in badminton clubs PB. Porwaja provided progress and opportunities for the badminton club PB. Porwaja maintains and produces both athletes - top athletes. The effect produced by the communion pattern of the star or all those channels is the effect on the internal badminton club PB. Porwaja. This internal effect then had an effect on the external environment of the badminton club PB. Porwaja. Interpersonal communication at the badminton club PB. Porwaja was effective enough because the feedback was going on. The coach used GPA (goal, planning, action) methods to deliver training programs. Communication patterns used in pb badminton clubs. PB. Porwaja is a star communication pattern or all channels because every athlete and trainer are free to discuss without restriction without staying within the bounds of decency. Keyword : PB. Porwaja, Interpersonal Communication, GPA Methods